From an Enhanced Understanding to Commercially Viable Electrodes: The Case of PTCLi4 as Sustainable Organic Lithium‐Ion Anode Material. (13th February 2017) - Iordache, Adriana; Bresser, Dominic; Solan, Sébastien; Retegan, Marius; Bardet, Michel; Skrzypski, Jonathan; Picard, Lionel; Dubois, Lionel; Gutel, Thibaut
Abstract : Organic active materials are currently considered to be the most promising technology for the realization of fully sustainable secondary batteries. However, the understanding of the underlying reaction mechanisms is still at its beginning. In this paper, an in‐depth investigation of tetra‐lithium perylene‐3, 4, 9, 10‐tetracarboxylate as a lithium‐ion anode model compound is presented, which can be easily synthesized from commercially available 3, 4, 9, 10‐perylene‐tetracarboxylic‐dianhydride. The results reveal that the lithium uptake is limited to two lithium ions per molecule along a two‐phase equilibrium potential within an operational voltage range down to 0.1 V. Below the corresponding potential plateau at 1.1 V the origin of the extra capacity is solely related to the presence of large amounts of conductive carbon. Based on these findings, optimized electrode composites with increased active material ratios of up to 95 wt% and a total active material mass loading of about 12.0 mg cm −2, that is, remarkably augmented areal capacities (≈1.2 mAh cm −2 ), using percolating carbon nanotubes as electron conductor and environment‐friendly, fluorine‐free aqueous binders, are developed. In addition to the more than tenfold increase in areal capacity, these optimized electrode compositions show enhanced first cycle coulombic efficiencies, thus providing a great leap forward toward their commercial exploitation. Abstract : The utilization of organic active materials would enable fully sustainable rechargeable batteries. However, besides a lack of in‐depth understanding regarding the underlying electrochemical reactions, reported electrode compositions are far from commercial relevance. Using tetra‐lithium perylene‐3, 4, 9, 10‐tetracarboxylate as model compound, these two issues are addressed, determining, first, the occurring de‐/lithiation reaction, and second, developing electrodes with a capacity of 1.2 mAh cm −2 .